A hospital-based study on the incidence, severity and risk factors of retinopathy of prematurity - Belekar, Neelam; Jadhav , Maheshwari (International Journal of Contemporary Pediatrics, 2025)
Background: Retinopathy of prematurity (ROP) is a leading cause of preventable childhood blindness in India. Improved neonatal survival has increased its incidence, necessitating region specific data on risk factors and disease severity in Western Maharashtra. Objectives of the study were to determine the incidence and severity of ROP and identify associated maternal and neonatal risk factors in a hospital setting. Methods: A cross-sectional study was conducted on 86 preterm infants (<34 weeks or <2000g) admitted to a NICU in Kolhapur. Infants were screened for ROP by a paediatric ophthalmologist using Retcam or indirect ophthalmoscopy. Demographic, clinical, and risk factor data were collected. Statistical analysis was performed using statistical package for the social sciences (SPSS) to compare variables between severe and non-severe ROP groups. Results: Out of 86 newborns screened, 23 developed ROP. Incidence of ROP was 26.7%. Among 23 neonates with ROP, the majority (47.8%) were born at 31–32 weeks gestation and 56.5% weighed 1–1.5 kg. Stage 1 ROP was most common (47.8%). Severe ROP was present in 39.1% of cases. Birth weight <1 kg (p=0.049) and need for mechanical ventilation (p=0.021) were significantly associated with severe ROP. The mean duration of oxygen therapy was significantly longer in the severe group (22.44 versus 13.93 days, p=0.043). A high prevalence of anaemia (78.3%) and sepsis (82.6%) was observed, though not statistically significant for severity. Conclusion: Low birth weight, prolonged oxygen therapy, and mechanical ventilation are significant risk factors for severe ROP. Targeted screening and optimized neonatal care are essential to reduce vision-threatening ROP.